Dukungan Sosial dengan Penerimaan Diri Remaja yang Melakukan Pernikahan Dini Pada Masa Pandemi COVID-19 - Jurita Natalia Selanno; Sri Aryanti Kristianingsih (Bulletin of Counseling and Psychotherapy, 2022)
The problem regarding the number of early marriages in Indonesia during the COVID-19 pandemic is immensely increasing due to various factors. Teenagers with cases of early marriage during the COVID-19 pandemic must receive and get various social supports so the teenager can adjust and accept every circumstance. This study aims to determine the relationship between social support and the self-acceptance of adolescents who marry prematurely during the COVID-19 pandemic. The research method in this study is a correlational quantitative method. The participants in this study were 61 teenagers who had early marriages during the COVID-19 pandemic, which were determined using a non-probability sampling technique, namely accidental sampling. The study's results found a significant positive relationship between social support and self-acceptance of adolescents who married prematurely during the COVID-19 pandemic, with a correlation coefficient of r = 0.418 and a significance value of 0.000 (p < 0.05).